Geothermal systems and energy resources : Turkey and Greece - Baba, Alper; Bundschuh, Jochen; Chandrasekharam, D. (Sustainable energy developments, 2014)
In the region comprised by Turkey and Greece, people have been using water from geothermal sources for bathing and washing of clothes since ancient times. This region falls within the Alpine-Himalayan orogenic belt and hence is locus of active volcanism and tectonism and experiences frequent seismic events. This volcanic and tectonic activity has given rise to over 1500 geothermal springs. Its importance has been recognized decades ago and the geothermal water is being utilized now for district heating, industrial processing, domestic water supply, balneology and electric power generation.